Stranger – Other – Muslim. On the Integration of Muslim Minorities in Europe (from an Anthropological and Cultural Perspective) - Wachowski, Jacek (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2024)
The article aims to characterize the sources of conflicts and social tensions related to the presence of the Muslim minority in Europe. To achieve this goal, I intend to utilize a transdisciplinary strategy that will enable the comparison of research results emerging from political science and sociological studies, as well as cultural studies and anthropology. This approach allows for the formulation of new diagnoses. On the one hand, it makes it possible to describe the main integration strategies regarding the Muslim minority in Europe and shows their insufficiency and ineffectiveness. On the other hand, it reminds us that migration and ethnic issues are rooted in theoretical reflection, preceding the phenomena analyzed in empirical research. It also draws attention to hidden mechanisms that determine the tendency to ethnic isolation and describes cultural processes that may contribute to remodeling the relationship between Muslim immigrants and their social environment. Celem artykułu jest scharakteryzowanie źródeł konfliktów i napięć społecznych, związanych z obecnością mniejszości muzułmańskiej w Europie. Realizacji tego celu służyć będzie przyjęcie strategii transdyscyplinarnej, umożliwiającej porównanie wyników badań powstających na gruncie studiów politologicznych i socjologicznych, z pracami kulturoznawczo-antropologicznymi. Ujęcie takie pozwala na sformułowanie nowych rozpoznań. Z jednej strony, umożliwia opisanie głównych strategii integracyjnych dotyczących mniejszości muzułmańskiej w Europie i pokazuje ich niewystarczalność oraz nieskuteczność. Z drugiej przypomina, że problematyka migracyjna i etniczna zakorzeniają się w refleksji teoretycznej, poprzedzającej analizowane w badaniach empirycznych zjawiska. Zwraca ponadto uwagę na ukryte mechanizmy decydujące o skłonnościach do etnicznej izolacji, a także opisuje procesy kulturowe, które mogą przyczynić się do przemodelowania relacji między imigrantami muzułmańskimi i ich społecznym otoczeniem.
Obcy – Inny – muzułmanin. O integracji mniejszości muzułmańskich w Europie (z perspektywy antropologiczno-kulturowej)
Keywords: Muslim minority; immigrants; Other; Strangers; integration processes; mniejszość muzułmańska; imigranci; Inny; Obcy; procesy integracyjne